Evaluation of the Alexon-Trend ProSpecT Campylobacter Microplate Assay - Tolcin, Rita (American Society for Microbiology, 2000)
We evaluated stool specimens known to contain or be free of Campylobacter by traditional culture, using the ProSpecT Campylobacter microplate assay (Alexon-Trend, Ramsey, Minn.). This rapid enzyme immunoassay for the detection of Campylobacter-specific antigens demonstrated 96% sensitivity and 99% specificity and is an acceptable alternative method of Campylobacter detection.